Suspected adenovirus causing an emerging Hepatitis among children below 10 years: a review - Rabaan, Ali A; Bakhrebah, Muhammed A.; Nassar, Majed S.; Natto, Zuhair S.; Al Mutair, Abbas; Alhumaid, Saad; Aljeldah, Mohammed; Garout, Mohammed; Alfouzan, Wadha A.; Alshahrani, Fatimah S.; Sulaiman, Tarek; AlFonaisan, Meshal K.; et al. (MDPI, 2022)
In October 2021, a case of acute hepatic failure without any known cause was identified in the United States of America. Upon further investigation, other children aged 1–6 years were reported to have the same liver failure, and some of them were positive for adenovirus 41 type F. On 21 April 2022, the Centers for Disease Control and Prevention (CDC) released an alert after 74 cases were identified in United Kingdom (UK) between 5 and 8 April in children below 10 years of age, some of whom were also found to be positive for SARS-CoV-2. All the patients showed symptoms such as vomiting, diarrhea, jaundice, and abdominal pain. The patients’ liver enzymes were remarkably increased. A total of 650 cases had been reported from 33 countries as of 27 May 2022, among which 222 cases were reported in the UK alone. No connection with SARS-CoV-2 or its vaccine has been found so far. However, the suspected cause is adenovirus, including its genomic variations, because its pathogenesis and laboratory investigations have been positively linked. Until further evidence emerges, hygiene precautions could be helpful to prevent its spread.